ANTIOXIDANTS, SUCROSE AND AGAR IN THE IN VITRO MULTIPLICATION OF Eremanthus incanus - Miranda, Natane Amaral; Titon, Miranda; Pereira, Israel Marinho; Fernandes, José Sebastião Cunha; Santos, Marcone Moreira; Oliveira, Rafaela Naiara de (Floresta, 2018)
The objective of this study was to evaluate the in vitro multiplication of Eremanthus incanus axillary buds in the presence of PVP additives and activated charcoal under the interaction of different sucrose and agar concentrations. Explants containing axillary buds were inoculated in MS culture medium to evaluate the effect of 0.8 g L-1 of PVP and 1.0, 2.0 and 4.0 g L-1 of activated charcoal. The results of the addition of 0, 15, 30, and 60 g L-1 of sucrose combined with concentrations of 6 and 10 g L-1 of agar in MS medium were also evaluated. The number and quality of emitted shoots were evaluated after 30 and 60 days. The addition of PVP to the culture medium was more efficient than the use of activated charcoal in the multiplication of the species. The presence of sucrose is indispensable for developing the shoots well, and the use of a lower concentration of agar favors the development of quality shoots. The best results for shoot multiplication were obtained using 30 g L-1 sucrose and 6 g L-1 agar. PVP, activated charcoal, agar and sucrose are important components in the culture medium and alter the in vitro multiplication of Eremanthus incanus.